Multi-year stability of spatial patterns in capelin otolith-edge chemical fingerprints in the Gulf of St. Lawrence, Canada - Romaric Jac; Lola Coussau; Elisabeth van Beveren; Mathieu Boudreau; Olivier Le Pape; Dominique Robert; Pablo Brosset; Pascal Sirois (Fisheries Research, 2026)

Drivers of growth in strong year classes of the deepwater redfish ( Sebastes mentella ) population from the Gulf of St. Lawrence derived from otolith increment‐based growth chronologies - Lola Coussau; Olivier Morissette; Dominique Robert; Pascal Sirois (Journal of Fish Biology, 2024)
The case of the deepwater redfish ( Sebastes mentella ) in the Gulf of St. Lawrence (GSL) is a compelling example of drastic fluctuations in annual recruitment strength, characteristic of spasmodic stocks. After three decades of low abundance, the emergence of three consecutive strong year classes in 2011–2013 resulted in an unprecedented increase in biomass. In spasmodic stocks such as GSL redfish, strong year classes sustain both the biomass and catch for decades. Therefore, understanding the growth dynamics of these cohorts is essential. In the present study, we reconstructed the annual growth rates of redfish using otolith increment‐based annual chronology and investigated the drivers of growth variation in redfish strong year classes of the early 2010s and early 1980s. Stock biomass was identified as the main extrinsic driver of redfish growth, suggesting intense competition for food at high conspecific density. Warming of deep waters in the GSL, where adult redfish settle, positively correlated with individual growth. However, recent warming of the cold intermediate layer showed a negative correlation with redfish growth, likely related to the shrinking of the habitat this water mass provides for various redfish cold‐water prey rather than to a direct effect of temperature. Reconstruction of redfish annual growth trajectories from birth to capture emphasized the importance of carryover effects in the growth potential of strong year classes. This work provided an important first outlook of the factors driving growth variation in GSL redfish spasmodic stock and explored midterm consequences of density‐dependent pressures on biological parameters of the population.

Connectivity of Greenland halibut in the northwestern Atlantic Ocean inferred from otolith chemistry - Laélien Bassi; Rejean Tremblay; Olivier Morissette; Pascal Sirois (Frontiers in Marine Science, 2024)
Greenland Halibut ( Reinhardtius hippoglossoides ) is a deepwater flatfish having a circumpolar distribution. Understanding the spatial connectivity and migratory patterns of this commercially valuable species is essential for ensuring a sustainable fishery; nonetheless, this information remains relatively scarce for many Greenland Halibut populations. Here we evaluate the connectivity and the population structure of halibut along coastal Greenland and Canada to better characterize the contribution of each production zone to the various stocks found in the northwestern Atlantic Ocean. In 2014 and 2016, we sampled 411 large Greenland Halibut from coastal Nunavut, Labrador, and Greenland. We used the elemental fingerprint (magnesium, strontium, and barium) from the otolith core and margin of the sampled fish to determine spatial differentiation of the source areas of the collected halibut. From the 17 sample sites, margin elemental fingerprint delineated four “elemental sectors”, representing pooled adjacent sites having similar chemistry. Overall, 62% of Greenland Halibut were correctly assigned to their sampled coast. Elemental fingerprint of the otolith cores indicated three chemically distinct natal sources for the captured halibut. The chemical record in the otolith cores suggested a high connectivity of Greenland Halibut in the northwestern Atlantic and a main natal source located potentially along the west coast of Greenland. Given that our results suggest the presence of a large nursery around Disko Bay–Hellefiske Bank, protection measures should be considered for this area.

Spatiotemporal variability in otolith elemental fingerprint and the potential to determine deepwater redfish (Sebastes mentella) origins and migrations in the Estuary and Gulf of St. Lawrence, Canada - Lola Coussau; Dominique Robert; Pascal Sirois (Fisheries Research, 2023)

Life in the fast lane: Revisiting the fast growth—High survival paradigm during the early life stages of fishes - Dominique Robert; Jun Shoji; Pascal Sirois; Akinori Takasuka; Ignacio A. Catalán; Arild Folkvord; Stuart A. Ludsin; Myron A. Peck; Su Sponaugle; Patricia M. Ayón; Richard D. Brodeur; Emily Y. Campbell; et al. (Fish and Fisheries, 2023)
Early life survival is critical to successful replenishment of fish populations, and hypotheses developed under the Growth‐Survival Paradigm (GSP) have guided investigations of controlling processes. The GSP postulates that recruitment depends on growth and mortality rates during early life stages, as well as their duration, after which the mortality declines substantially. The GSP predicts a shift in the frequency distribution of growth histories with age towards faster growth rates relative to the initial population because slow‐growing individuals are subject to high mortality (via starvation and predation). However, mortality data compiled from 387 cases published in 153 studies (1971–2022) showed that the GSP was only supported in 56% of cases. Selection against slow growth occurred in two‐thirds of field studies, leaving a non‐negligible fraction of cases showing either an absence of or inverse growth‐selective survival, suggesting the growth‐survival relationship is more complex than currently considered within the GSP framework. Stochastic simulations allowed us to assess the influence of key intrinsic and extrinsic factors on the characteristics of surviving larvae and identify knowledge gaps on the drivers of variability in growth‐selective survival. We suggest caution when interpreting patterns of growth selection because changes in variance and autocorrelation of individual growth rates among cohorts can invalidate fundamental GSP assumptions. We argue that breakthroughs in recruitment research require a comprehensive, population‐specific characterization of the role of predation and intrinsic factors in driving variability in the distribution and autocorrelation of larval growth rates, and of the life stage corresponding to the endpoint of pre‐recruited life.

Feeding ecology of redfish ( Sebastes sp.) inferred from the integrated use of fatty acid profiles as complementary dietary tracers to stomach content analysis - Sarah Brown‐Vuillemin; Réjean Tremblay; Denis Chabot; Pascal Sirois; Dominique Robert (Journal of Fish Biology, 2023)
In the northern Gulf of St. Lawrence (nGSL), redfish ( Sebastes mentella and Sebastes fasciatus combined) are at record levels of abundance following the strong recruitment of three consecutive cohorts in 2011–2013 and have become by far the most abundant demersal fish in the region. Understanding redfish trophic relationships is essential for the effective management and conservation of species in the nGSL ecosystem. To date, description and quantification of redfish diet in the region have been restricted to conventional stomach content analysis (SCA). Using analysis of fatty acid (FA) profiles as complementary dietary tracers, the authors conducted multivariate analyses on 350 livers of redfish which were collected in combination with stomach contents during a bottom‐trawl scientific survey in August 2017. The predator FA profiles were compared to those of eight different redfish prey types identified as dietary important with SCA. Results suggested similitude between SCA and FA results, with zooplankton prey being more related to small (

Diet composition of redfish (Sebastes sp.) during periods of population collapse and massive resurgence in the Gulf of St. Lawrence - Sarah Brown-Vuillemin; Denis Chabot; Claude Nozères; Réjean Tremblay; Pascal Sirois; Dominique Robert (Frontiers in Marine Science, 2022)
Redfish ( Sebastes mentella and S. fasciatus ) are back at spectacular record high levels in the Gulf of St. Lawrence (GSL) and the effects of this massive resurgence on other components of the food web remain largely unknown. To better understand the trophic implications of the surging redfish biomass within the GSL ecosystem, 3,690 stomachs containing food were collected during two periods: one characterised by low redfish abundance (1993–1999) and the other during a period of record abundance (2015–2019). Taxonomical analysis of stomach contents from individuals of different sizes from three subareas of the GSL was carried out to determine diet composition during both periods. Zooplankton represented the main prey category for small redfish (< 20 cm), which was driven by a predation on amphipods, mostly Themisto sp. in North-East Gulf, in the 1990s and on copepods of the genus Calanus in the deep channels and euphausiids in North-West Gulf in the 2010s. Themisto sp. still dominated the diet of medium (20–30 cm) redfish in the 1990s while the copepods were predominant during the 2010s. Shrimp consumption increased with redfish size and two species were particularly important in large redfish diet (≥ 30 cm) during both periods: pink glass shrimp ( Pasiphaea multidentata ), mostly in the Laurentian Channel and northern shrimp ( Pandalus borealis ), especially in North-East Gulf. Redfish predation on shrimp represents a major concern for the dynamics of the northern shrimp which supports a valuable fishery in the GSL but has been declining in abundance since several years. Piscivory was observed in large redfish diet, with capelin ( Mallotus villosus ) being the major fish prey in the 1990s and redfish (cannibalism) in the 2010s, suggesting density-dependent control at high density of small redfish. By presenting a detailed overview into the redfish diet composition and its temporal variability, the present study offers a first look into the possible future trophic impacts of a resurging groundfish in the GSL ecosystem.

Thermal adaptation rather than demographic history drives genetic structure inferred by copy number variants in a marine fish - Hugo Cayuela; Yann Dorant; Claire Mérot; Martin Laporte; Eric Normandeau; Stéphane Gagnon‐Harvey; Marie Clément; Pascal Sirois; Louis Bernatchez (Molecular Ecology, 2021)
Increasing evidence shows that structural variants represent an overlooked aspect of genetic variation with consequential evolutionary roles. Among those, copy number variants (CNVs), including duplicated genomic regions and transposable elements (TEs), may contribute to local adaptation and/or reproductive isolation among divergent populations. Those mechanisms suppose that CNVs could be used to infer neutral and/or adaptive population genetic structure, whose study has been restricted to microsatellites, mitochondrial DNA and Amplified fragment length polymorphism markers in the past and more recently the use of single nucleotide polymorphisms (SNPs). Taking advantage of recent developments allowing CNV analysis from RAD‐seq data, we investigated how variation in fitness‐related traits, local environmental conditions and demographic history are associated with CNVs, and how subsequent copy number variation drives population genetic structure in a marine fish, the capelin ( Mallotus villosus ). We collected 1538 DNA samples from 35 sampling sites in the north Atlantic Ocean and identified 6620 putative CNVs. We found associations between CNVs and the gonadosomatic index, suggesting that six duplicated regions could affect female fitness by modulating oocyte production. We also detected 105 CNV candidates associated with water temperature, among which 20% corresponded to genomic regions located within the sequence of protein‐coding genes, suggesting local adaptation to cold water by means of gene sequence amplification. We also identified 175 CNVs associated with the divergence of three previously defined parapatric glacial lineages, of which 24% were located within protein‐coding genes, making those loci potential candidates for reproductive isolation. Lastly, our analyses unveiled a hierarchical, complex CNV population structure determined by temperature and local geography, which was in stark contrast to that inferred based on SNPs in a previous study. Our findings underline the complementarity of those two types of genomic variation in population genomics studies.

Shared ancestral polymorphisms and chromosomal rearrangements as potential drivers of local adaptation in a marine fish - Hugo Cayuela; Quentin Rougemont; Martin Laporte; Claire Mérot; Eric Normandeau; Yann Dorant; Ole K. Tørresen; Siv Nam Khang Hoff; Sissel Jentoft; Pascal Sirois; Martin Castonguay; Teunis Jansen; et al. (Molecular Ecology, 2020)
Gene flow has tremendous importance for local adaptation, by influencing the fate of de novo mutations, maintaining standing genetic variation and driving adaptive introgression. Furthermore, structural variation as chromosomal rearrangements may facilitate adaptation despite high gene flow. However, our understanding of the evolutionary mechanisms impending or favouring local adaptation in the presence of gene flow is still limited to a restricted number of study systems. In this study, we examined how demographic history, shared ancestral polymorphism, and gene flow among glacial lineages contribute to local adaptation to sea conditions in a marine fish, the capelin ( Mallotus villosus ). We first assembled a 490‐Mbp draft genome of M. villosus to map our RAD sequence reads. Then, we used a large data set of genome‐wide single nucleotide polymorphisms (25,904 filtered SNPs) genotyped in 1,310 individuals collected from 31 spawning sites in the northwest Atlantic. We reconstructed the history of divergence among three glacial lineages and showed that they probably diverged from 3.8 to 1.8 million years ago and experienced secondary contacts. Within each lineage, our analyses provided evidence for large N e and high gene flow among spawning sites. Within the Northwest Atlantic lineage, we detected a polymorphic chromosomal rearrangement leading to the occurrence of three haplogroups. Genotype–environment associations revealed molecular signatures of local adaptation to environmental conditions prevailing at spawning sites. Our study also suggests that both shared polymorphisms among lineages, resulting from standing genetic variation or introgression, and chromosomal rearrangements may contribute to local adaptation in the presence of high gene flow.

Impacts of stocking and its intensity on effective population size in Brook Charr (Salvelinus fontinalis) populations - Philippine Gossieaux; Louis Bernatchez; Pascal Sirois; Dany Garant (Conservation Genetics, 2019)

Introgressive hybridization between wild and domestic individuals and its relationship with parasitism in brook charr Salvelinus fontinalis - Philippine Gossieaux; Pascal Sirois; Louis Bernatchez; Dany Garant (Journal of Fish Biology, 2018)
The effects of introgression on parasitism in brook charr Salvelinus fontinalis were investigated in 28 lakes with various levels of stocking in Québec, Canada. No effect of genetic background on parasitism was found at the individual level. Body length seemed to explain most of the variation observed at this level, with largest fish being more infected. However, lakes with the greater average domestic genetic background were found to display significantly lower parasite prevalence and diversity. Since our results indicate no effect of domestic genes at the individual level, the negative association with introgression found at the population level may be mainly attributed to differences in intrinsic environmental quality of lakes ( e.g . fishing pressure, availability of food resources, abiotic characteristics).

Do genetic drift and accumulation of deleterious mutations preclude adaptation? Empirical investigation using RAD seq in a northern lacustrine fish - Charles Perrier; Anne‐Laure Ferchaud; Pascal Sirois; Isabel Thibault; Louis Bernatchez (Molecular Ecology, 2017)
Understanding genomic signatures of divergent selection underlying long‐term adaptation in populations located in heterogeneous environments is a key goal in evolutionary biology. In this study, we investigated neutral, adaptive and deleterious genetic variation using 7,192 SNP s in 31 Lake Trout ( Salvelinus namaycush ) populations ( n = 673) from Québec, Canada. Average genetic diversity was low, weakly shared among lakes, and positively correlated with lake size, indicating a major role for genetic drift subsequent to lake isolation. Putatively deleterious mutations were on average at lower frequencies than the other SNP s, and their abundance relative to the entire polymorphism in each population was positively correlated with inbreeding, suggesting that the effectiveness of purifying selection was negatively correlated with inbreeding, as predicted from theory. Despite evidence for pronounced genetic drift and inbreeding, several outlier loci were associated with temperature and found in or close to genes with biologically relevant functions notably related to heat stress and immune responses. Outcomes of gene–temperature associations were influenced by the inclusion of the most inbred populations, in which allele frequencies deviated the most from model predictions. This result illustrates challenge in identifying gene–environment associations in cases of high genetic drift and restricted gene flow and suggests limited adaptation in populations experiencing higher inbreeding. We discuss the relevance of these findings for the conservation and management, notably regarding stocking and genetic rescue, of Lake Trout populations and other species inhabiting highly fragmented habitats.

Investigating the extent of parallelism in morphological and genomic divergence among lake trout ecotypes in Lake Superior - Alysse Perreault‐Payette; Andrew M. Muir; Frederick Goetz; Charles Perrier; Eric Normandeau; Pascal Sirois; Louis Bernatchez (Molecular Ecology, 2017)
Understanding the emergence of species through the process of ecological speciation is a central question in evolutionary biology which also has implications for conservation and management. Lake trout ( Salvelinus namaycush ) is renowned for the occurrence of different ecotypes linked to resource and habitat use throughout North America. We aimed to unravel the fine genetic structure of the four lake trout ecotypes in Lake Superior. A total of 486 individuals from four sites were genotyped at 6822 filtered SNP s using RAD seq technology. Our results revealed different extent of morphological and genetic differentiation within the different sites. Overall, genetic differentiation was weak but significant and was on average three times higher between sites (mean F ST = 0.016) than between ecotypes within sites (mean F ST = 0.005) indicating higher level of gene flow or a more recent shared ancestor between ecotypes within each site than between populations of the same ecotype. Evidence of divergent selection was also found between ecotypes and/or in association with morphological variation. Outlier loci found in genes related to lipid metabolism and visual acuity were of particular interest in this context of ecotypic divergence. However, we did not find clear indication of parallelism at the genomic level, despite the presence of phenotypic parallelism among some ecotypes from different sampling sites. Overall, the occurrence of different levels of both genomic and phenotypic differentiation between ecotypes within each site with several differentiated loci linked to relevant biological functions supports the presence of a continuum of divergence in lake trout.

Fully Equipped to Succeed: Migratory Contingents Seen as an Intrinsic Potential for Striped Bass to Exploit a Heterogeneous Environment Early in Life - Olivier Morissette; Frédéric Lecomte; Guy Verreault; Michel Legault; Pascal Sirois (Estuaries and Coasts, 2016)

Historical introgression and the role of selective vs. neutral processes in structuring nuclear genetic variation (AFLP) in a circumpolar marine fish, the capelin ( Mallotus villosus ) - GABRIEL J. COLBECK; JULIE TURGEON; PASCAL SIROIS; JULIAN J. DODSON (Molecular Ecology, 2011)
The capelin ( Mallotus villosus ) is a widespread marine fish species for which previous work has identified geographically distinct mtDNA clades, the frontiers of which are well within adult and larval dispersal capabilities. Here, we use AFLPs to test for the presence of nuclear gene flow among clades. In addition, we evaluate genetic structuring within one clade, the Northwest Atlantic (NWA). We found that each of the mtDNA clades corresponds with a unique nuclear DNA genetic cluster. Within the NWA clade, we detected individuals with small but significant amounts of genetic ancestry from other clades, likely due to historical introgression. Further support for historical introgression comes from analyses of variance in locus‐specific differentiation, which support introgression between some clades and divergence without gene flow between others. Within the NWA, we identified two genetic clusters that correspond to sites in geographically adjacent areas. However, these clusters differ primarily at ‘outlier’ loci, and a genetic subdivision ( K = 2) was not supported by genetic clustering programs using neutral loci. Significant neutral F ST differentiation was found only between sites that otherwise differed at outlier loci. Thus, these populations may be in the initial stages of ‘isolation by adaptation’. These results suggest strong between‐clade reproductive isolation despite opportunities for gene flow and support the hypothesis that selection can contribute to divergence in otherwise ‘open’ systems.

Historical variability of subfossil chironomids (Diptera: Chironomidae) in three lakes impacted by natural and anthropogenic disturbances - Vicky Tremblay; Isabelle Larocque-Tobler; Pascal Sirois (Journal of Paleolimnology, 2010)